2016
DOI: 10.1155/2016/8920503
|View full text |Cite
|
Sign up to set email alerts
|

Nationality, Gender, Age, and Body Mass Index Influences on Vitamin D Concentration among Elderly Patients and Young Iraqi and Jordanian in Jordan

Abstract: Vitamin D is necessary for maintaining and regulating calcium levels; thus, insufficiency of vitamin D increases the risk of many chronic diseases. This study aimed to examine vitamin D levels among Jordanian and Iraqi volunteers and find the relation between vitamin D level and lipid profile patients. Vitamin D levels were evaluated using enzyme-linked immunosorbent assay. For young healthy group subjects, vitamin D levels were 20.60 ± 5.94 ng/mL for Jordanian and 27.59 ± 7.74 ng/mL for Iraqi. Vitamin D conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 55 publications
7
36
6
1
Order By: Relevance
“…228 Despite the obvious sex-dependent differential availability and tissue distribution of vitamin D in the human body, 229 the efficacy of the administered burden of exogenous vitamin D also depends on body mass index, dietary habits, lifestyle, age, nationality, vitamin D 2 availability, VDR, and CYP polymorphisms. 230,231 Nutritional recommendations regarding vitamin D supplementation should take into account these issues. However, vitamin D should be considered in those populations confronting an immune challenge and/or nutritional starvation (eg, in pregnancy, infants, elderly, those with chronic illnesses).…”
Section: Pro-survival Features Of Vitamin D: Role In Clinicsmentioning
confidence: 99%
“…228 Despite the obvious sex-dependent differential availability and tissue distribution of vitamin D in the human body, 229 the efficacy of the administered burden of exogenous vitamin D also depends on body mass index, dietary habits, lifestyle, age, nationality, vitamin D 2 availability, VDR, and CYP polymorphisms. 230,231 Nutritional recommendations regarding vitamin D supplementation should take into account these issues. However, vitamin D should be considered in those populations confronting an immune challenge and/or nutritional starvation (eg, in pregnancy, infants, elderly, those with chronic illnesses).…”
Section: Pro-survival Features Of Vitamin D: Role In Clinicsmentioning
confidence: 99%
“…Another finding of the present study is that male patients have higher serum vitamin D levels compared to female patients with recurrent aphthous stomatitis. There are conflicting results among the studies regarding vitamin D level differences by gender in the literature [ 23 , 24 ]. Al-Horani et al [ 23 ], found the serum vitamin D concentrations in young males and females were 25.82 ng/ml and 21.95 ng/mL, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In Middle East countries, high variation in serum 25(OH)D levels was revealed. The lowest level of 3.6 ng/ml (9 nmol/L) was seen in a study conducted on older persons in Saudi Arabia [2]. Vitamin D is a prohormone that has a key role in calcium and phosphate balance and bone structure [3,4].…”
Section: Introductionmentioning
confidence: 98%
“…With all the medical advances of the century, vitamin D deficiency is as yet plagued. Over a billion people worldwide are vitamin D deficient or insufficient [2]. In Middle East countries, high variation in serum 25(OH)D levels was revealed.…”
Section: Introductionmentioning
confidence: 99%